Impact of physiotherapy on fall prevention in patients with Parkinson’s disease (Research, Society and Development, 2025)
Parkinson’s disease (PD) is a chronic, progressive neurological condition that is primarily manifested by four motor signs: muscle rigidity, slowness of voluntary movements, resting tremors, and postural instability. It is a progressive disease that may cause disability, dependence, and even immobility, thereby increasing the risk of falls, which are among the most frequent complications. The aim of this study is to verify the impact of physiotherapy on fall prevention in patients with Parkinson's disease. The literature indicates that the combination of different physiotherapeutic techniques enhances improvements in PD symptoms, such as aerobic exercises, stretching, muscle strengthening, rehabilitation, and muscle strengthening associated with proprioceptive exercises, which aim to improve the patient’s body awareness and motor response in situations that require rapid postural adjustments. Thus, this project consists of an integrative literature review, based on secondary data available on platforms such as the Scientific Electronic Library Online (SCIELO), Medical Literature Analysis and Retrieval System Online (MEDLINE), PubMed, and Google Scholar. After selecting the articles, 30 were identified, and 22 were used. A critical content analysis was carried out, organizing the studies according to their objectives, methodology, main findings, and clinical relevance. Therefore, it is concluded that there is a need for broader dissemination of evidence-based rehabilitation protocols and for the continuous training of physiotherapy professionals, encouraging effective, safe interventions adapted to the individual needs of each patient.